Carbohydrate-electrolyte ingestion enhances cognitive performance during a cross-country mountain biking race - Pomportes-Castagnet, L.; Hays, A.; Gajdos, T.; Brisswalter, J.; Davranche, K. (PsyArXiv, 2021)
To assess the influence of carbohydrate-electrolyte (CHO-E) intakes on cognitive and physical performances, we carried out an ecological protocol simulating the load variations of a biking race. Eight well-trained athletes completed an outdoor mountain biking time-trial race (TT) (19.6 ± 0.40 km length; 81 min ± 15 min) interspersed with three 10 min varied-load cycling exercises while performing a Simon task and a Critical Flicker Fusion task in laboratory. A splitted drink of 1150 ml of either 7% CHO-E solution (fructose 89%, maltodextrin 11%) or placebo (PL) was administered. Results suggest that the TT induces a decrease of cortical arousal (p = 0.28) and an impairment of efficiency (p < .001) during a decision-making task in the PL condition, while the reverse was observed with CHO-E ingestions. Furthermore, a better accuracy (p = .05) and a lower perceived effort (p = .05) were also observed with CHO- E intakes whatever the TT duration. As a conclusion, ingestion of a 7% CHO-E solution during a prolonged outdoor TT decreases perceived effort and restricts exercise-induced cognitive performance impairment. CHO-E ingestion appears to be an effective means of delaying the central nervous system fatigue during high-intensity intermittent exercise performed in an ecological context.